THE AGE OF INFORMATION OVERLOAD: ARE WE SMARTER OR JUST BUSIER? - Rakhmatullayeva Durdona Yakubjon kizi (Modern American Journals, 2025)
In the 21st century, society has entered an unprecedented era of information abundance. With the rise of the internet, social media, and instant communication, individuals are bombarded with data at every turn. While access to information has democratized knowledge and accelerated innovation, it has also introduced significant challenges, such as reduced attention spans, decision fatigue, and the illusion of productivity. This paper uses the IMRAD format to explore whether modern humans are becoming more intelligent or merely more preoccupied, drawing on research from cognitive science, communication theory, and digital sociology.
Keywords: Information overload, digital age, cognitive capacity, multitasking, productivity, attention span, knowledge economy, mental fatigue, decision fatigue, digital literacy